Novel configuration of polyimide matrix-enhanced cross-linked gel separator for high performance lithium ion batteries. (20th June 2016) - Zhang, Hong; Zhang, Yin; Yao, Zhikan; John, Angelin Ebanezar; Li, Yang; Li, Weishan; Zhu, Baoku
Highlights: For the first time, a cross-linked gel polymer electrolyte with additional lithium ions, was introduced into a nonwoven separator. The PI nonwoven is employed to ensure enhanced thermal stability and mechanical strength of the IACS. With the introduction of PAMPS(Li + ), the migration and mobility rate of anions could be hindered by the -SO3 − group, giving rise to a high lithium ion transference number. This IACS is recommended as a promising candidate for the high-power and high-safety lithium ion batteries. Abstract: A novel composite nonwoven separator exhibiting high heat resistance, high ionic conductivity and high lithium ion transference number is fabricated by a simple dip-coating and heat treatment method. The thermal stable polyimide (PI) nonwoven matrix is chosen as a mechanical support and contributes to improving the thermal shrinkage of the composite nonwoven separator (abbreviated as IACS). The cross-linked poly(2-acrylamido-2-methylpropanesulfonic acid) PAMPS(Li + ) gel polymer electrolyte (GPE), lithium ion sources of a single ion conductor, is introduced into the PI nonwoven matrix and acts as a functional filler. This PAMPS (Li + ) GPE is proved to be able to provide internal short circuit protection, to alleviate liquid electrolyte leakage effectively, to supply more lithium ions dissociating from PAMPS (Li + ) by liquid electrolyte solvent, to contribute a more stable interfacial resistance, and thus resulting in an excellent cyclability. More notably, the migration and mobility rate of anions could be hindered by the −SO3 − group in the PAMPS (Li + ) polymer based on electrostatic interaction, giving rise to a very high lithium ion transference number. These fascinating characteristics endow the IACS a great promise for the application in the high power and high safety lithium ion batteries.